Performance Evaluation of Acoustic Firing Localization Systems and Sniper Projectile Trajectory Detector - علي مسعود; شحادة الموسى (Latakia University Journal -Engineering Sciences Series, 2023)
In recent years, in-air acoustic sensing systems have been developed to locate small arms fire, and a number of countries have systems in various stages of development that have used them in operations. These systems are mounted on a soldier’s helmet or on vehicles to provide crews with better situational awareness, thus enhancing crew safety and troop protection. The performance measures proposed in this study were derived for open terrain, a typical environment for most test sites around the world. The gauges are for individual matrix systems rather than distributed sensor networks that use triangulation and/or integration with other sensors for detection and recognition. Due to the increasing number of sniper attacks in crises, estimation of direction of sound wave arrival (DOA) based on time differences between separate sensors is usually applied in order to identify the source of the sound, in this paper, a method is proposed to estimate the state of a sniper shot, i.e. bullet trajectory recognition The method relies on mathematical modeling of the projectile’s shock wave, and the use of simulations, sniper data, caliber, and weather conditions to test and verify the performance of the proposed method.